Defects in Synaptic Plasticity, Reduced NMDA-Receptor Transport, and Instability of Postsynaptic Density Proteins in Mice Lacking Microtubule-Associated Protein 1A - Takei, Yosuke (J Neurosci, 2015)
Microtubule-associated protein 1A (MAP1A) is a member of the major non-motor microtubule-binding proteins. It has been suggested that MAP1A tethers NMDA receptors (NRs) to the cytoskeleton by binding with proteins postsynaptic density (PSD)-93 and PSD-95, although the function of MAP1A in vivo remains elusive. The present study demonstrates that mouse MAP1A plays an essential role in maintaining synaptic plasticity through an analysis of MAP1A knock-out mice. The mice exhibited learning disabilities, which correlated with decreased long-term potentiation and long-term depression in the hippocampal neurons, as well as a concomitant reduction in the extent of NR-dependent EPSCs. Surface expression of NR2A and NR2B subunits also decreased. Enhanced activity-dependent degradation of PSD-93 and reduced transport of NR2A/2B in dendrites was likely responsible for altered receptor function in neurons lacking MAP1A. These data suggest that tethering of NR2A/2B with the cytoskeleton through MAP1A is fundamental for synaptic function. SIGNIFICANCE STATEMENT This work is the first report showing the significance of non-motor microtubule-associated protein in maintaining synaptic plasticity thorough a novel mechanism: anchoring of NMDA receptors to cytoskeleton supports transport of NMDA receptors and stabilizes postsynaptic density scaffolds binding to NMDA receptors. Newly generated mutant mice lacking MAP1A exhibited learning disabilities and reduced synaptic plasticity attributable to disruptions of the anchoring machinery.